Hoffmann's House : Memoria de exposiciones 2000-2003 en Santiago de Chile. - Cuadros, Ricardo; Diaz, Gonzalo; Johnson, José Ignacio; Machuca, Guillermo; Navarro, Mario; Pulido, Gerardo; Santa Cruz, Guadalupe; Vergara, Rodrigo; Viveros, Cristian (Santiago de Chile : Hoffmann's House, 2004)
Araya, Lorena ; Atria, Magdalena ; Bravo, Victor Hugo ; Bucci, Andres ; Cabieses, Jorge ; Carvajal, Paz ; Ceppi, Alvaro ; Céspedes, Juan ; Colectivo P/A ; Diaz, José Pablo ; Diaz, Juan Pablo ; Downey, Juan ; Egaña, Lucia ; El Nuevo Cine Chileno ; Fernandez, Diego ; Fernandez & Schalscha ; Gajardo, Mauricio ; Garcia, Francisca ; Garcia, Isabel ; Garcia de la Sierra, Eduardo ; Guerra, Luis Enrique Silvestre ; Ibarra, Carolina ; Iglesis, Matias ; Krause, Rainer ; La Banda ; Las Hueonas ; Letelier, Michelle ; Lewin, Consuelo ; Lopez, Carlos ; Louit, Cristian ; Marambio, Benjamin ; Marin, Livia ; Mellado, Pablo ; Moraga, Marcela ; Mujica, Felipe ; Navarrete, Carlos ; Navarro, Mario ; Pavez, Victor ; Perez, Ivan ; Portus, Leonardo ; Purdy, Caterina ; Ramirez, Francisco ; Redondo, Carolina ; Rivas, Macarena ; Rivas, Tomas ; Rivera, Pablo ; Silva, Christián ; Stewart, Malu ; Soro, Mario ; Torres, Claudio ; Valenzuela, Valeria ; Vergara, Rodrigo ; Viera-Gallo, Manuela ; Villablanca, Joe ; Wildi, Ingrid
Engels
Spaans
boek